Узагальнена теорія Де Рама - Ходжа для трансмутаційних операторів Дельсарта у багатовимірному випадку та її застосування (Нелінійні коливання, 2004)
A study of spectral and differential-geometric properties of Delsartetransmutation operators is given. Their differential geometrical andtopological structure in multidimension is analyzed, the relationships withDe Rham-Hodge-Skrypnik theory of generalized differential complexes arestated. Some applications to integrable dynamical systems theory inmultidimension are presented.